Índice de mobilidade urbana sustentável : uma contribuição ao método a partir da aplicação na cidade de Passo Fundo - Scheffer, Ana Paula (2020)
Human actions to mitigate the impacts caused to the environment and to minimize the consumption of natural resources are an indispensable condition for maintaining life on earth. In this context, sustainability emerges as a motto: integrating with the complex systems that make up a city or region to promote a balance. This perception has been gradually integrating a new perspective of contemporary life, linking efforts all over the world (examples like 2030 Agenda), through shared actions, from the global to the local sphere. Sustainable urban mobility is part of this context since it aims at addressing several issues such as traffic congestion and accidents, stress, air pollution, and others, which have been frequently detected in large cities and directly affect the environment and life quality of the population. Those facts show the importance of this system for the management of a city, besides the promotion of the quality of life. Following these ideas, this study focuses on mobility to understand the problems that are related to the theme, seeking tools that aim to interpret the situation of sustainable urban mobility of a municipality or region and promote improvements based on a careful analysis of priorities. For this, it was required to conduct a search and select an analysis method - the Sustainable Urban Mobility Index (IMUS). Also, the research had as specific objectives: to calculate the IMUS of Passo Fundo; stipulate a future score based on the relationship between the index indicators and the municipal planning instruments; critically evaluate the methodology adopted in order to contribute to its improvement, and finally, to present an overview of mobility between medium-sized cities that have the calculated index. As a result, for the current situation, Passo Fundo obtained a score of 0.457, identifying the possibility of an increase of 25% after the implementation of actions apart from the Mobility Plan and other documents that aim to plan and manage the urban territory. When defining an overview of mobility, among the municipalities, it was possible to identify the indicators with the worst performances and relate them to Brazil’s National Urban Mobility Policy, verifying if the policy has the potential to encourage the improvement of scores. In view of the analyzed results, the quality of the proposed plans stands out, however, it warns about the monitoring and effectiveness of actions, since the median result denotes large gaps in sustainable urban mobility; which need to be filled in order to increase the quality of life of the population, as well as a greater balance with the environment.